LAJU PERKEMBANGAN LAPORAN KASUS PENYAKIT UNGGAS DI KOTA YOGYAKARTA - , DEQI A EFKANDO, Roza Azizah Primatika, S. Si., M. Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Poultry is the most abundant animals maintained humans. Easy maintenance and poultry sales price is very tempting. It is enough to make strengthen the poultry farmers as a farm for a living. Along with the many poultry farmers both in small and large scale, poultry disease monitoring should be carried out. In Yogyakarta, almost in every corner village, would find poultry. Poultry farmers in Yogyakarta included in the group of small-scale. General domestic poultry is free-range chicken, chicken game, ornamental chickens, ducks, turkeys, geese, ducks, quail, and ornamental birds for pets. The aim of the Field Internship (1) Determine the type of disease affecting poultry in the city of Yogyakarta (2) Knowing the rate of progression of the disease in poultry Yogyakarta (3) Knowing the handling of poultry diseases in the city of Yogyakarta. Some poultry diseases such as Avian Influenza (AI), Newcastle Disease (ND) and Infectious Bursal Disease (IBD) has a rate of spread of the disease is short and wide, also has a high rate of mortality poultry. Spread of disease progression in Yogyakarta, in 2012 the number of cases of the disease amounted to AI: 12 cases